Comparison of iCT-based navigation and fluoroscopic-guidance for atlantoaxial screw placement in 78 patients with traumatic cervical spine injuries - Gierse, Jula; Mandelka, Leon Eric; Medrow, Antonia; Bullert, Benno; Grützner, Paul Alfred; Franke, Jochen; Vetter, Sven Y. (European spine journal, 2024)
Studies have shown biomechanical superiority of cervical pedicle screw placement over other techniques. However, accurate placement is challenging due to the inherent risk of neurovascular complications. Navigation technology based on intraoperative 3D imaging allows highly accurate screw placement, yet studies specifically investigating screw placement in patients with traumatic atlantoaxial injuries are scarce. The aim of this study was to compare atlantoaxial screw placement as treatment of traumatic instabilities using iCT-based navigation or fluoroscopic-guidance with intraoperative 3D control scans.